The Training of Learning Media Development based on Adobe Flash Creative Suite 6 (CS6) for Elementary School Teachers - Siti Halidjah; Asmayani Salimi; Hery Kresnadi (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2021)
The purpose of this Community service   is to provide teachers with knowledge, understanding and skill of the developing of learning media based on adobe flash creative suite 6 (CS6) through training. Ten participants attended the activity. The form of activity chosen is training and guidance. The training was held for one day. The training is more focused on the practice of making learning media. Giving direct theory along with the practice of preparing learning media. Based on training activities in community service  , it can be concluded that the teacher's understanding of learning media based on Adobe Flash Creative Suite 6 (CS6) is getting better. Teachers can use Adobe Flash Creative Suite 6 (CS6) to package prepared content into attractive learning media.